Diagnóstico De La Producción De Textos Descriptivos En Inglés - Eulalia, Rojas Castro Carmita; Alejandra, Logroño Becerra Mónica; Iván, Lara Olivo Lenin; Maribel, Yumi Guacho Lorena (European Scientific Journal, ESJ, 2018)
The objective of the current research was to diagnosis the descriptive texts production as complement of the communicational skill in English, from the students of third level "M" from the Language Center from Escuela Superior Politécnica de Chimborazo in October 2016 - March 2017. For this reason, an intervention plan was applied with an evaluation rubric, to an intentional sample or a control group composed of 1 teacher and 41 students. The rubric was verified and validated by academic peers, who ratified the fulfilment of writing stages such as, prewriting, drafting, review, editing, and proofreading. The intervention lasted eight weeks, where the students carried out a set of activities that were qualified and quantified through a checklist with a weighted range of options. The research is descriptive, field and bibliographic. The information obtained was tabulated, analyzed and interpreted; the same determined the current scenario of the students in each of the stages for the descriptive texts production, obtaining as a conclusion about that a strategy is needed to influence on the production of descriptive texts.